PENGARUH HUMAN CAPITAL EFFICIENCY, RELATIONAL CAPITAL EFFICIENCY, CAPITAL EMPLOYED EFFICIENCY, DAN SITUASI KRISIS EKONOMI GLOBAL TERHADAP NON PERFORMING LOANS, PERUSAHAAN PERBANKAN DI INDONESIA TAHUN 2007-2015 - Todo Tondi Betha Samosir; Saarce Elsye Hatane (Business Accounting Review, 2017)
The aim of this study was to analyze the influence of Human Capital Efficiency, Relational Capital Efficiency, Capital Employed Efficiency, and Situation of economic crisis on Financial Performance measured by using Non Performing Loans. The population used in this study consisted of conventional banking companies. Sample was chosen by using purposive sampling method that obtained 11 banking companies in Indonesia.The hypothesis in this study was tested by using linear regression model. Simultaneous signification test ( F test), and partial signification (t test) with  = 10% were used to test the hypothesis in this study. The result of F test by using NPL showed HCE, RCE, CEE, and Situation of Economic Crisis had a significant influence on NPLThe result of t test partially showed that variables of HCE, CEE, and Situation of Economic Crisis had a significant influence on NPL. While RCE variable had no significant influence on NPL